The IEEE GRSS Brazil Chapter: 2020 Activities [Chapters] - Estrabis N.V. (2022)
© 2013 IEEE.The IEEE Geoscience and Remote Sensing Society (GRSS) Brazil Chapter comprises 49 professionals and 57 student members, totaling 106 members in 2020. The following Chapter officers performed services during 2020